Application of additive manufacturing/3D printing technologies and investment casting for prototype development of polycrystalline diamond compact (PDC) drill bit body - Altaf, K. (Asian Research Publishing Network, 2016)
This study is about the application of Additive Manufacturing (AM) technologies for the manufacturing of an improved design of Polycrystalline Diamond Compact drill bit body by using Thermojet three dimensional printing and investment casting. The aim of study is to investigate a faster and effective PDC drill bit manufacturing process without compromising the mechanical aspects of the fabricated model. The conventional fabrication processes could be lengthy and cost intensive for the development of a complex product. With the rapidly developing technologies, the aspiration of manufacturing rate is keep rising and will be higher in future for sure. To overcome these issues, AM is one of the tool between the manufacturing rate and high precision product. In the current study, a computer aided design (CAD) of PDC bit body model that was modified from a previous design was taken and sectioned into parts to optimize the three dimensional printing process. Wax patterns were created using AM in separate sections for minimizing the support structure. Then the drill bit body was casted using investment casting process. The end result was a PDC drill bit body fabricated with steel materia. Â© 2006-2016 Asian Research Publishing Network (ARPN).